Efforts to Increase Public Knowledge Regarding Dagusibu (Obtain, Use, Store, and Dispose of Medicines) in Keteleng Village, Tragah District, Bangkalan Regency - Nurul Jannah; Octaviana Dyah Oentari (Institute of Advanced Knowledge and Science, 2026)
Improper medication management remains a public health problem, particularly in self-medication practices. Lack of knowledge about how to obtain, use, store, and dispose of medications can increase the risk of medication errors, therapeutic failure, antibiotic resistance, and environmental pollution from household drug waste. The DAGUSIBU (Obtain, Use, Store, and Dispose of Drugs) program is an educational effort to improve public literacy in the rational use of medications. This study aims to analyze the increase in community knowledge after being educated about the DAGUSIBU principles in Keteleng Village, Tragah District, Bangkalan Regency. The activity used an educational approach with a one-group pretest-posttest design. The intervention was carried out through counseling using interactive lectures, discussions, questions and answers, and educational media such as PowerPoint, leaflets, and posters. Evaluation was carried out using pretest and posttest questionnaires consisting of 10 questions and participated by 15 participants. The results showed that the number of correct answers increased from 127 (84.67%) in the pretest to 129 (86.00%) in the posttest, while the number of incorrect answers decreased from 23 (15.33%) to 21 (14.00%). Based on changes in individual scores, 5 participants (33.3%) experienced an increase in scores, 6 participants (40.0%) achieved a stable score, and 4 participants (26.7%) experienced a decrease in scores. In addition to the improvement in evaluation results, observations during the activity showed that participants had a better understanding of the principles of obtaining medicines from authorized pharmaceutical facilities, using medicines according to regulations, storing medicines based on their characteristics, and safely disposing of damaged or expired medicines. The success of the activity was supported by active community participation, village government support, and the use of various educational media, although its implementation still faced obstacles such as limited time for counseling and differences in participant characteristics. Thus, DAGUSIBU-based education can be an effective health promotion strategy to increase public knowledge about rational drug management and needs to be implemented sustainably as part of efforts to improve public health.